What’s in a name? : Sense and Reference in biodiversity information - Philipson, Joakim (Stockholm University, 2017)
"That which we call a rose by any other name would smell as sweet.” Shakespeare has Juliet tell her Romeo that a name is just a convention without meaning, what counts is the reference, the 'thing itself', to which the property of smelling sweet pertains alone. Frege in his classical paper “Über Sinn und Bedeutung” was not so sure, he assumed names can be inherently meaningful, even without a known reference. And Wittgenstein later in Philosophical Investigations (PI) seems to deny the sheer arbitrariness of names and reject looking for meaning out of context, by pointing to our inability to just utter some random sounds and by that really implying e.g. the door. The word cannot simply be separated from its meaning, in the same way as the money from the cow that could be bought for them (PI 120). Scientific names of biota, in particular, are often descriptive of properties pertaining to the organism or species itself. On the other hand, in semantic web technology and Linked Open Data (LOD) there is an overall effort to replace names by their references, in the form of web links or Uniform Resource Identifiers (URIs). “Things, not strings” is the motto. But, even in view of the many "challenges with using names to link digital biodiversity information" that were extensively described in a recent paper, would it at all be possible or even desirable to replace scientific names of biota with URIs? Or would it be sufficient to just identify equivalence relationships between different variants of names of the same biota, having the same reference, and then just link them to the same “thing”, by means of a property sameAs(URI)? The Global Names Architecture (GNA) has a resolver of scientific names that is already doing that kind of work, linking names of biota such as Pinus thunbergii to global identifiers and URIs from other data sources, such as Encyclopedia of Life (EOL) and uBio Namebank. But there may be other challenges with going from a “natural language”, even from a not entirely coherent system of scientific names, to a semantic web ontology, a solution to some of which have been proposed recently by means of so called 'lexical bridges'.
Keywords: Computer and Information Science; Medicine, Health and Life Sciences; Metadata; PID system; Biodiversity; Taxonomy; Medical and Health Sciences; Medicin och hälsovetenskap; Computer and Information Sciences; Data- och informationsvetenskap (datateknik)